"Imagine Neuro-Oncology"- a one week course with medical and technical students: students' reflections about multidisciplinarity and its practical relevance. Issue 2 (3rd March 2020) - Scheide, Laura; Huber, Thomas; Bette, Stefanie; Nest, Alexandra; Zimmer, Claus; Berberat, Pascal O; Kreiser, Kornelia
ABSTRACT: Modern medicine requires tight multidisciplinary collaboration and communication among several technical disciplines. Nevertheless, multidisciplinary medical courses are rare and even less often scientifically evaluated. The aim was to evaluate an innovative neuro-oncology course for medical students (MED) and students of science, technology, engineering, and mathematics (STEM) so that they learn and practice mutual understanding, communication and cooperation. 10 MED and 9 STEM were trained together during a one-week-course on the topic of "brain tumor" in imaging, surgical planning, surgery, pathological diagnosis, and adjuvant therapy. Evaluation was undertaken via focus groups and accompanying questionnaires about motivation, course acceptance, and multidisciplinary attitude. Students evaluated course structure, content, and multidisciplinary setting positively and showed high intrinsic motivation. However, the students sensed an "artificial dividing line" between both groups, which was conceptually encouraged by the deliberate temporary subdivision into "monodisciplinary" seminars and during the preparation of presentations. Students' opinion of the concept was generally positive as they learned about the challenges in finding a "common scientific language". Nevertheless, some criticisms were raised concerning the dividing line between the disciplines, which in part led to organizational changes. Even though the current reality may be reflected here, the goal of future interprofessional courses should definitely be to dissolve this dividing line.